2022
DOI: 10.1128/jvi.01415-21
|View full text |Cite
|
Sign up to set email alerts
|

Structures of Two Human Astrovirus Capsid/Neutralizing Antibody Complexes Reveal Distinct Epitopes and Inhibition of Virus Attachment to Cells

Abstract: Human astrovirus is an important cause of viral gastroenteritis worldwide. Young children, the elderly, and the immunocompromised are especially at risk for contracting severe disease. However, no vaccines exist to combat human astrovirus infection. Evidence points to the importance of antibodies in enabling protection of healthy adults from reinfection. To develop an effective subunit vaccine that broadly protects against diverse astrovirus serotypes, we must understand how neutralizing antibodies target the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 49 publications
(58 reference statements)
0
8
0
Order By: Relevance
“…The characterization of the neutralization mechanisms of the reported anti-VA1 Nt-MAbs, together with the identification of the actual epitopes of the antibodies on the virus spike by structural biology approaches, as has been previously shown for classical HAstV (17), will aid in identifying virus functional sites required for astrovirus cell entry. This information will be relevant for the development of prophylactic and therapeutic approaches to address this neurotropic astrovirus strain.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The characterization of the neutralization mechanisms of the reported anti-VA1 Nt-MAbs, together with the identification of the actual epitopes of the antibodies on the virus spike by structural biology approaches, as has been previously shown for classical HAstV (17), will aid in identifying virus functional sites required for astrovirus cell entry. This information will be relevant for the development of prophylactic and therapeutic approaches to address this neurotropic astrovirus strain.…”
Section: Discussionmentioning
confidence: 97%
“…These two polypeptides are derived from a capsid precursor protein of 86 kDa (VP86) processed intracellularly by an undefined protease (14). Previously, the antigenic sites of neutralizing monoclonal antibodies (Nt-MAbs) to the capsid spike domain of classical HAstVs have been mapped (15)(16)(17). However, despite the medical relevance of the non-classical HAstV-VA1, there is limited information about its antigenic sites.…”
Section: Introductionmentioning
confidence: 99%
“…The SJ001 strain of MuAstV has a unique two-amino-acid deletion in relation to similar MuAstV strains between residues 535 and 536 (TTXXGAE) within the extended tip of the loop region of the β8-β9 hairpin, which suggests that this loop may also be under particular selective pressure. Interestingly, all previous structurally characterized neutralizing antibodies that target the HAstV spike have been found to predominantly target loop regions, and have also been shown to prevent the spike from attaching to cells [30], likely by preventing receptor binding. The functional significance of the loops is not known, but given their high variability, their immunodominance could potentially aid the virus by drawing antibodies towards regions of the spike in which the virus can readily mutate without significant consequence to escape neutralization, unlike a functional receptor-binding domain, which faces selective pressure to remain conserved to maintain viral fitness.…”
Section: Discussionmentioning
confidence: 99%
“…These data, in conjunction with previous mouse vaccinations with recombinant HAstV spike, show that recombinant astrovirus spikes are able to induce anti-spike IgG antibody responses. Although it is currently unknown if the anti-MuAstV spike IgG antibodies are neutralizing (there is not yet an in vitro MuAstV infection model to test them), it has previously been shown that antibodies elicited by vaccination with recombinant HAstV spike are capable of neutralizing HAstV in cell culture and can also block HAstV spike attachment to human Caco2 cells [30,31]. Notably, we show that recombinant MuAstV spike vaccination can induce higher levels of anti-spike IgG antibody than MuAstV infection in vivo, as was seen in three of the four mice tested, which presents promising potential to immunize mice against MuAstV using a recombinant spike-based vaccine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation